UPAYA MENGHADAPI PERUBAHAN LINGKUNGAN STRATEGIS DENGAN MEMBANGUN DAN MERAIH COMPETITIVE ADVANTAGE MELAUI VALUE CHAIN ANALYSIS DAN KEMITRAAN - MIRDAH, ANDI; INDRA TENAYA, AGUS (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 3 No 1 (2008))
The success of an organization to operate in a complex and tight competition is very much determined by several factors. Global business changes phenomena have demanded the companies to be more critical. Only those having global competitive advantage would sustain and develop. To identify sources of and potential competitive advantage, an organization would need value chain concept as an analytical tool. According to the concept, a company needs to develop partnership relation in the whole activities from beginning till ending. This article reviews how companies manage their strategic activities using value chain analysis and how this concept would be developed in the partnership relation.
Keywords: competitive advantage, value chain, partnership